Equity valuation : Sotipapier - Fakhfakh, Mariem (2017)
This dissertation aims to value the equity of a Tunisian company :Sotipapier. As pointed in the corporate finance literature review -under the first section of the dissertation-, distinct valuations methods usually result in different outcomes. In order to increase the robustness of the fair value of the share price, I use the DCF method as well as the relative valuation approach. Indeed, each method applied generates slightly distinct valuations. Therefore, I Consider an average share price of two approaches that yields a share price of 4.54 TND -for the end of FY 2015 .In a fur-ther step, I compare in the last section the results that I find with a recent valuation of Soti-papier‟s equity performed by KPMG -Tunisia in mid 2015. The comparison highlight a diver-gence of 5.3% that falls within a reasonable margin given the particular context of each valuation.